Parka: Porang sweet potatoes with kenikir leaves for analog rice to anti T2DM / Bistis Kautsarisma Istadza Kumala ... [et al.] - Kumala, Bistis Kautsarisma Istadza; Yuda, Wayan Wira; Ul Akrimah, Yasma Aziza; Khasanah, Khairul Magfirah; Hikmaranti, Maulida (2020)
Type 2 Diabetes Mellitus (T2DM) is one of diseases that has clinical symptoms like insulin resistance and caused by an unhealthy lifestyle that consumes many foods with high glycemic levels. One of way to prevent hyperglycemia is to consume foods with a low glycemic index. Porang, have the lowest glycemic index values among other tubers. Considering that porang are still rarely used, an innovation, is analog rice from porang sweet potatoes fortified with kenikir leaves as an antidiabetic food for T2DM patients. Quercetin from kenikir leaves can reduce glycemic levels without eliminating carbohydrate content. Tests were carried out in vivo by mice with 6 different group treatment and in silico by docking to determine the effectiveness of this analog rice. Another test is the organoleptic test on 100 people to determine the feasibility of this rice for consumption. The results of the in vivo test showed that DMP group treatment with diabetic has decrease the glycemic index after fed by the analog rice, organoleptic test showed that the rice was acceptable for consumption by people with type 2 diabetes mellitus. In silico test show that glucomannan porang and quercetin kenikir can inhibit the type 2 diabetes by Nf-Kb pathway.